Peningkatan Kemampuan Memahami Perubahan Wujud Melalui Video Interaktif Berbasis CTL pada Siswa Slow Learner : Improving the Ability to Understand Changes in State of Matter Among Slow Learners Using CTL-Based Interactive Videos - Neli Mailawati; Rendy Roos Handoyo (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study was motivated by the low ability of second-grade elementary school students—specifically those at risk of being "slow learners"—to understand changes in the states of matter, a topic involving abstract science concepts. The study aimed to improve the learning process and comprehension of changes in the states of matter through the implementation of interactive videos based on the Contextual Teaching and Learning (CTL) approach. A Classroom Action Research (CAR) method was employed over two cycles, comprising planning, action implementation, observation, and reflection. The research subjects were two students identified as being at risk of being slow learners. Data were collected via tests, observation, and documentation, then analysed using both quantitative and qualitative descriptive methods. The results indicate that the use of CTL-based interactive videos enhanced the quality of the learning process, evidenced by increased student engagement in observing, questioning, discussing, and connecting the material to daily experiences. This improvement in the learning process led to better student learning outcomes. Subject RF's score rose from 30% at the baseline to 90% by the end of Cycle II, while Subject AB's score increased from 40% to 90%. The class average learning outcome rose from 61 to 96, and the mastery rate increased from 22% to 100% by the end of Cycle II. Based on these findings, it is concluded that CTL-based interactive videos are effective in improving the learning process and the understanding of changes in the states of matter for students at risk of being slow learners, making them a suitable alternative instructional medium for science education in elementary schools.